2021
DOI: 10.1016/j.anaerobe.2021.102384
|View full text |Cite
|
Sign up to set email alerts
|

Did Clostridioides difficile testing and infection rates change during the COVID-19 pandemic?

Abstract: Testing for and incidence of infection (CDI) was examined at a single center before and during the first surge of the COVID-19 pandemic. Incidence of CDI remained stable but testing statistically significantly decreased during the first surge despite an increase in antibiotic use. There were no new CDI-focused antimicrobial stewardship interventions introduced during this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 7 publications
0
21
1
1
Order By: Relevance
“…Data on the incidence of HA-CDI in COVID-19 patients is still scarce and disparate ( 5 8 , 14 , 17 21 ) several studies describe a lower incidence of CDI during the pandemic ( 5 8 ). As summarized by Granata et al, most studies find a lower or equal incidence of CDI in the first phase of the pandemic than in the pre-pandemic period ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data on the incidence of HA-CDI in COVID-19 patients is still scarce and disparate ( 5 8 , 14 , 17 21 ) several studies describe a lower incidence of CDI during the pandemic ( 5 8 ). As summarized by Granata et al, most studies find a lower or equal incidence of CDI in the first phase of the pandemic than in the pre-pandemic period ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…A consequence of increased antibiotics prescription in COVID-19 is gut dysbiosis, that creates a favorable environment for C. difficile . However, Hawes et al reported a stable incidence of CDI during the first peak of the pandemic, despite increasing clindamycin, cefotaxime, ceftriaxone, ceftazidime, and quinolone consumption [ 46 ]. Similarly, other authors reported a decreased incidence of CDI that proved the positive effect of intensified cleaning measures together with reduced patient mobility [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in nine hospitals in Massachusetts reports that about 40% of patients with COVID‐19 have experienced diarrhea after admission and that two of these patients, critically ill, died prior to receiving a correct therapy for CDI [ 50 ] ( Table 1 ). Some single-center studies have reported a trend toward decreased C. difficile testing and a stable or decreased CDI incidence [ 51 , 52 ] ( Table 1 ). These results could be partially explained with a potential over- or inappropriate testing in the pre-COVID-19 period or more thoughtful testing during the current pandemic.…”
Section: And the Covid-19 Pandemicmentioning
confidence: 99%
“…The underdiagnosis of CDI has already been recognized as an alarming issue in the pre-pandemic period, with about 40 000 inpatients with this infection potentially undiagnosed in European hospitals every year due to the absence of clinical suspicion and/or suboptimal diagnostic laboratories in the pre-pandemic period [ 71 ]. Recent studies have reported a trend toward decreased C. difficile testing in several hospitals [ 47 , 49 , 51 , 52 ] ( Table 1 ), suggesting that the COVID‐19 pandemic may lead to a further underreporting of CDI and highlighting the importance of a differential diagnosis of CDI in patients with COVID-19.…”
Section: What About CDI In the Next Future?mentioning
confidence: 99%